Influence of non-thermal processing techniques on sulfur dioxide and oxygen concentrations in young and aged wines - Lukić, Katarina, prehrambena biotehnologinja (Array, 2020)
The application of innovative techniques like high hydrostatic pressure (HHP) and high power ultrasound (HPU) for food processing and preservation is one of the current topics in food science. In the enological field, these techniques have been identified as alternative methods for wine microbial stabilization and acceleration of wine aging process. Due to lack of available information about their influence on physicochemical characteristics, the aim of this work was to study the effect of HHP and HPU on sulfur dioxide and dissolved oxygen concentrations in red and white wines. The effect was evaluated immediately after the treatment and after 3, 6 and 12 months of aging in bottles. Moreover, the synergistic effect of mentioned techniques along with antioxidants additions (glutathione and SO2) was also evaluated. The results showed that the concentrations of free and total SO2 did not change immediately after HHP treatments, while after HPU processing there was no clear trend in analyzed parameters. As expected, results showed that both, free and total SO2 decreased during storage period of red and white wines. Regarding both applied techniques, slightly higher concentrations of free SO2 were observed in samples treated by HHP after 12 months of storage. Oxygen concentration slightly increased immediately after the treatments, with the highest concentration determined after HPU processing. During aging, its concentrations decreased and were similar or slightly higher than of those determined in untreated samples. Regarding the antioxidants additions, better protective effect was obtained by addition of higher concentration of SO2 than glutathione, since these samples were characterized by lower concentrations of dissolved oxygen.